2013
DOI: 10.1097/wnn.0000000000000002
|View full text |Cite
|
Sign up to set email alerts
|

Alexithymia and Empathy Predict Changes in Autonomic Arousal During Affective Stimulation

Abstract: High alexithymia and high empathy scores were linked to increased autonomic arousal at the onset of emotional stimulation, but were distinguishable in the rates of habituation of the evoked arousal. Our data provide insight into the relationships among interacting psychological traits, physiologic regulation, and the arousal dimension of emotional experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 79 publications
2
14
0
7
Order By: Relevance
“…Then, through cognitive processing in cortical areas, including the insular, somatosensory, and various prefrontal regions, introspectively accessible experiences emerge. Findings from patients with autonomic failure and alexithymia (119), although superficially supportive, primarily show quantitative changes in subjective experience, more consistent with a modulatory role of body feedback.…”
Section: Emotions In Light Of the First-vs Higher-order Debatementioning
confidence: 75%
“…Then, through cognitive processing in cortical areas, including the insular, somatosensory, and various prefrontal regions, introspectively accessible experiences emerge. Findings from patients with autonomic failure and alexithymia (119), although superficially supportive, primarily show quantitative changes in subjective experience, more consistent with a modulatory role of body feedback.…”
Section: Emotions In Light Of the First-vs Higher-order Debatementioning
confidence: 75%
“…Sterlini and Bryant [46] showed that hyperarousal and anxiety were strongly predictive for peritraumatic dissociation in first-time skydivers. At the same time, increased autonomic arousal and slower habituation after exposure to negative emotional stimuli have been shown to be associated with alexithymia [47]. Taylor et al [48] suggested that alexithymia as a response to stress is accompanied by prolonged states of emotional arousal.…”
Section: Discussionmentioning
confidence: 99%
“…Along these lines, only a few additional studies assessed habituation of physiological emotional responses in alexithymia: Bogdanov et al () and Rabavilas () showed impaired skin conductance habituation, but in contrast Pollatos et al () found no differences in heart rate and skin conductance between alexithymic and control participants during recovery from a social stressor. Papciak, Feuerstein, and Spiegel () also did not find group differences in recovery from stress while Connelly and Denney () found higher reactivity to a stressor during recovery but only in self‐report and not in physiology.…”
Section: Introductionmentioning
confidence: 99%